2011
DOI: 10.1111/j.1939-3938.2010.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the boundaries: How sexual assault nurse examiners (SANEs) balance patient care and law enforcement collaboration

Abstract: Forensic nursing is multidisciplinary in nature, which can create tensions for practitioners between their responsibilities to patient care and collaborations with law enforcement and prosecutors. Because there are compelling reasons grounded in both nursing theory and legal precedent to maintain separation, there is a pressing need to understand how sexual assault nurse examiner (SANE) programs successfully negotiate these potentially conflicting roles. The purpose of this study was to examine how SANEs defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
2
20
0
1
Order By: Relevance
“…Forcing strategies were primarily described by nurses. This aligns with research documenting how SANEs balance patient care and forensic demands, and often manage competing pressures from advocates and law enforcement by reinforcing the parameters of their role (Campbell, Greeson & Patterson, 2012; Maier, 2012a, 2012b). Almost every advocate described unobtrusive and resigned strategies, while only one or two nurses and law enforcement officers cited such strategies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Forcing strategies were primarily described by nurses. This aligns with research documenting how SANEs balance patient care and forensic demands, and often manage competing pressures from advocates and law enforcement by reinforcing the parameters of their role (Campbell, Greeson & Patterson, 2012; Maier, 2012a, 2012b). Almost every advocate described unobtrusive and resigned strategies, while only one or two nurses and law enforcement officers cited such strategies.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have suggested that rape crisis advocates experience anger and frustration stemming largely from repeatedly witnessing and hearing about law enforcement officers who mistreat victims, but also from communication barriers with other systems and the lack of referrals from law enforcement and health care practitioners (Maier, 2008; Payne, 2007; Ullman & Townsend, 2007; Wasco & Campbell, 2002). Forensic nurses also describe witnessing and hearing about the mistreatment of victims by other service providers as a cause of tension, and also suggest that relationships with other service providers are taxed when nurses perceive those providers as overstepping role boundaries (Campbell, Greeson, & Patterson, 2012; Maier, 2012a, 2012b). …”
Section: Conflict In Sartsmentioning
confidence: 99%
“…Thus, the nurses' compassionate approach may appear different than a compassionate response from advocates. Furthermore, the nurses believe that maintaining objectivity lends credibility to their expert witness testimony and the evidence yielded from their examinations (Campbell, Greeson, & Patterson, 2011). Therefore, the nurses and advocates appear to hold similar values of justice, caring, and respect, but these similarities appear nebulous to the nurses and advocates in the focal program.…”
Section: Discussionmentioning
confidence: 99%
“…Victims in contact with specialized treatment groups have been found more often to have evidence collection kits taken, which may enhance evidence collection (Campbell et al, 2005). Furthermore, research suggests that the focus on victim care has a positive effect on the emotional well-being of victims, which may make it more likely that victims are willing and able to participate in the legal process (Campbell et al, 2011;Campbell et al, 2008;McLaren et al, 2009;Stone et al, 2006). Contrary to our expectations we found no significant differences in attrition patterns and legal reasons for case closure between victims who had been in contact with the CRV and victims who had not.…”
Section: Discussionmentioning
confidence: 99%